2022
DOI: 10.3389/fimmu.2022.904823
|View full text |Cite
|
Sign up to set email alerts
|

Sphingolipid metabolism in T cell responses after allogeneic hematopoietic cell transplantation

Abstract: Allogeneic hematopoietic cell transplantation (allo-HCT) is an effective immunotherapy against hematopoietic malignancies. The infused donor lymphocytes attack malignant cells and normal tissues, termed a graft-verse-leukemia (GVL) effect and graft-verse-host (GVH) response or disease (GVHD), respectively. Although engineering techniques toward donor graft selection have made HCT more specific and effective, primary tumor relapse and GVHD are still major concerns post allo-HCT. High-dose systemic steroids rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 100 publications
(126 reference statements)
0
4
0
Order By: Relevance
“…Speci cally, we observed almost 2-fold increase in CerS2 and Cers5 expression in activated Th cells, which synthesize C22-/C24-/C26-Cer or C14-/C16-Cer, respectively 21,22 . In contrast, only slight changes were observed in the expression of CerS4 and CerS6, which produce C18-/C20-Cer or C14-/C16-Cer, respectively 21,22 . Consistent with the upregulation of CerS2, the proportion of Cer (d18:1/24:0) in ceramide lipids was signi cantly increased following TCR stimulation (from 8.19% in naïve CD4 + T cells to 26.9% in Th0 cells, 26.2% in Th1 cells, 21.4% in Th2 cells, 17.5% in Th17 cells, and 16.8% in iTreg cells).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Speci cally, we observed almost 2-fold increase in CerS2 and Cers5 expression in activated Th cells, which synthesize C22-/C24-/C26-Cer or C14-/C16-Cer, respectively 21,22 . In contrast, only slight changes were observed in the expression of CerS4 and CerS6, which produce C18-/C20-Cer or C14-/C16-Cer, respectively 21,22 . Consistent with the upregulation of CerS2, the proportion of Cer (d18:1/24:0) in ceramide lipids was signi cantly increased following TCR stimulation (from 8.19% in naïve CD4 + T cells to 26.9% in Th0 cells, 26.2% in Th1 cells, 21.4% in Th2 cells, 17.5% in Th17 cells, and 16.8% in iTreg cells).…”
Section: Discussionmentioning
confidence: 61%
“…Our proteomic analysis revealed that changes in the protein expression of CerS family upon TCR stimulation. Speci cally, we observed almost 2-fold increase in CerS2 and Cers5 expression in activated Th cells, which synthesize C22-/C24-/C26-Cer or C14-/C16-Cer, respectively 21,22 . In contrast, only slight changes were observed in the expression of CerS4 and CerS6, which produce C18-/C20-Cer or C14-/C16-Cer, respectively 21,22 .…”
Section: Discussionmentioning
confidence: 61%
“…Additionally, sphingolipids exert significant regulatory influence as major lipid components of the myelin sheath surrounding nerve axons. Consequently, a thorough exploration of sphingolipid metabolic processes holds the potential to inform future therapeutic strategies for glioblastoma 32 , 33 . Leveraging comprehensive transcriptome sequencing data, our study reinforces the notion that unraveling the biological significance of sphingolipid metabolic pathways could serve as a compelling driving force in the current therapeutic landscape of glioblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…The changes were associated with activation of mitochondrial metabolism [ 388 , 389 ]. Recent findings indicate a key role of sphingolipids in the regulation of cancer metabolism and anticancer immune responses [ 20 , 390 ]. Dramatic changes in sphingolipid composition and processing were reported in cancer tissues [ 391 ].…”
Section: Future Perspectives Of Tnf-α/trail Therapy and Clinical Appl...mentioning
confidence: 99%